Recommendations of the German Association of Urogynecology on functional sonography of the lower female urinary tract - Schär, Gabriel; Koelbl, H.; Voigt, R.; Merz, E.; Anthuber, Ch.; Niemeyer, R.; Ralph, G.; Bader, W.; Fink, D.; Grischke, Eva-Maria; Hanzal, E.; Koechli, O. R.; et al. (International urogynecology journal, 1996)
Ultrasound is a complementary evaluation for the study of female urinary incontinence which allows functionalmorphological documentation. A reliable urogynecologic examination is based on the patient's history, clinical evaluation, urodynamics and imaging. Training in sonography of the female lower urinary tract should be performed within the scope of urogynecological evaluations.
Gesehen am 06.05.2025